PLANETESIMAL SULFATE AND AQUEOUS ALTERATION IN CM AND CI CARBONACEOUS CHONDRITES - Airieau S.A.; Farquhar J.; Thiemens M.H.; Leshin L.A.; Bao H.; Young E. (My University, 2005)
Water-soluble sulfate salts extracted from six CM chondrites have oxygen isotope compositions that are consistent with an extraterrestrial origin. The Δ17O of sulfate are correlated with previously reported whole rock δ18O and with an index of meteorite alteration, and may display a correlation with the date of the fall. The enrichments and depletions for Δ17O of water-soluble sulfate from the CM chondrites relative to the terrestrial mass dependent fractionation line are consistent with sulfate formation in a rock dominated asteroidal environment, and from aqueous fluids that had undergone relatively low amounts of oxygen isotope exchange and little reaction with anhydrous components of the meteorites. It is unresolved how the oxidation of sulfide to sulfate can be reconciled with the inferred low oxidation state during the extraterrestrial alteration process. Oxygen isotope data for two CI chondrites, Orgueil and Ivuna, as well as the ungrouped C2 chondrite Essebi are indistinguishable from sulfate of terrestrial origin and may be terrestrial weathering products, consistent with previous assertions. Our oxygen isotope data, however, can not rule out a preterrestrial origin either.